2020
DOI: 10.1080/1359432x.2020.1833858
|View full text |Cite
|
Sign up to set email alerts
|

How do weekly obtained task i-deals improve work performance?The role of relational context and structural job resources

Abstract: Previous research on idiosyncratic deals (i-deals) has treated them as concrete events, arguing that these i-deals shape employment relationships and impact on work performance over long periods of time. However, some types of i-deals may be negotiated and shaped over short periods of time. The aim of this research is to understand the social context within which these types of i-deals unfold and influence employee work performance. Focusing on task ideals and adopting a weekly diary design approach, we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Given the role that workgroups play in influencing i-deals, it is important to understand whether i-deals in turn influence the workgroup. To date, researchers have usually investigated the outcomes of i-deals only at the individual level (e.g., Rofcanin et al, 2020; see Bal and Boehm, 2019 for an exception). Examining i-deals at higher levels of analysis is vital for understanding how one employee's i-deal can impact others, and how i-deals affect the groups or larger organizational units in which they occur (see Schriesheim et al, 2001).…”
Section: I-deals and Outcomes For The Workgroup: Group Performancementioning
confidence: 99%
“…Given the role that workgroups play in influencing i-deals, it is important to understand whether i-deals in turn influence the workgroup. To date, researchers have usually investigated the outcomes of i-deals only at the individual level (e.g., Rofcanin et al, 2020; see Bal and Boehm, 2019 for an exception). Examining i-deals at higher levels of analysis is vital for understanding how one employee's i-deal can impact others, and how i-deals affect the groups or larger organizational units in which they occur (see Schriesheim et al, 2001).…”
Section: I-deals and Outcomes For The Workgroup: Group Performancementioning
confidence: 99%
“…I‐ deals have been recently cast as dynamic, as they can be developed and negotiated over a short period of time and can vary continuously over time (Ng et al, 2021; Rofcanin et al, 2021). This conceptualization moves beyond previous frameworks of i ‐deals as static implementations that are negotiated ex ante or ex post and last for long periods of time (e.g., several years).…”
Section: Discussionmentioning
confidence: 99%
“…This conceptualization moves beyond previous frameworks of i ‐deals as static implementations that are negotiated ex ante or ex post and last for long periods of time (e.g., several years). Rofcnin et al (2021) found that coworker support relates to the successful obtainment of task i‐ deals that continue to evolve beyond the baseline arrangement. Relatedly, our findings point to the importance of organizational members' support for the negotiated ex ante i‐ deal.…”
Section: Discussionmentioning
confidence: 99%
“…In line with social exchange theory (Blau, 1964), employees will reciprocate support they receive. Indeed, social exchange theory has provided the guiding framework for i‐deals research, which has found that granting i‐deals leads to higher organizational citizenship behaviour (Anand et al, 2010) and task performance (Rofcanin et al, 2021; Rofcanin et al, 2018). Recipients of an i‐deal also show higher affective commitment (Ho and Tekleab, 2016; Hornung et al, 2008) and stay longer with the company (Bal et al, 2012; Las Heras et al, 2017).…”
Section: Background and Hypothesesmentioning
confidence: 99%